Social relationship for physical objects - Dawei Wei; Huansheng Ning; Yuke Qian; Tao Zhu (International Journal of Distributed Sensor Networks)
To apply the algorithms in Internet of Things for physical world objects, the relationship between physical objects is becoming more and more complicated. As we know, social relationship is widely used in human world and social Internet of Things to solve the multiple object problems. Thus, a way via combining social relationship with physical object to solve the problem with a huge number of objects or complicated interactions among objects has been analyzed. This article proposes a new concept of “Physical Objects’ Social Relationship” for describing, managing, and predicting the relationships between physical objects in Internet of Things. The classification method for physical objects’ social relationships is proposed using the spatial-temporal attribute of social relationships. Moreover, the logical expression method for physical objects’ social relationships is discussed.